Facile preparation of Poly(butylene succinate)/Carbon nanotubes/polytetrafluoroethylene ternary nanocomposite foams with superior electrical conductivity by synergistic effect of "ball milling" and supercritical fluid-Assisted processing. (5th January 2021) - Huang, An; Lin, Jialin; Chen, Shudong; Fang, Hui; Wang, Hankun; Peng, Xiangfang
Abstract: Conductive polymer composites (CPCs) with different types of polytetrafluoroethylene (PTFE) were prepared via melt mixing, and the cellular structure was introduced into poly (butylene succinate) (PBS) by the supercritical CO2 foaming technique. The carbon nanotubes (CNTs) had the best dispersion in the PBS/CNTs/PTFE-P5 composite (PTFE with a diameter of approximately 5–10 μm). The CNTs enhanced the crystallizability of PBS, and the addition of PTFE was more significant, especially PTFE-P5. The storage modulus increased, and a transition from liquid-like to solid-like behavior occurred at low frequencies. Adding PTFE dramatically improved the pore structure, leading to a two-orders-of-magnitude increase in pore density, especially for PTFE-P5. The conductivity ( δ ) of solid PBS/CNTs/PTFE-P5 was four times higher than that of PBS/CNTs. The δ values of all the foams were much higher than those of their solid counterparts, demonstrating that the introduction of a large number of pores optimized the dispersion of CNTs and further improved the electrical conductivity because of the formation of a more complete conductive network structure (CNS). In particular, the δ value of foamed PBS/CNTs/PTFE-P5 under 3 wt% CNT loading reached 54.05 S/m. The thermal and mechanical properties, as well as the thermal conductivity, were also investigated. This work provides a simple method to prepare flexible biodegradable CPCs with a highly dispersed CNT CNS under high melt viscosity conditions. Graphical abstract: Image 1 Highlights: Innovation to significantly improve the conductivity of CPCs by adding a third-phase polymer (PTFE-P5), which plays the role of "ball milling" Few articles reported to synergistically prepare high conductivity CPCs by adding high viscosity polymer and SCF foaming technology. First study on biodegradable polymer-based CPCs and foams with high conductivity by combining HAAKE mixer and batch foaming.